2015
DOI: 10.1007/s10965-015-0822-3
|View full text |Cite
|
Sign up to set email alerts
|

Optimized synthesis and swelling properties of a pH-sensitive semi-IPN superabsorbent polymer based on sodium alginate-g-poly(acrylic acid-co-acrylamide) and polyvinylpyrrolidone and obtained via microwave irradiation

Abstract: A pH-sensitive superabsorbent hydrogel composite, sodium alginate-g-poly(acrylic acid-co-acrylamide) in the presence of polyvinylpyrrolidone (PVP), was prepared using the semi-interpenetrating polymer network (semi-IPN) technique and microwave irradiation. Potassium peroxodisulfate (KPS) was used as an initiator, N,N,N′,N′-tetramethylene diamine (TEMED) as a reaction accelerator, and N,N′-methylene bisacrylamide (MBA) as a crosslinker. The Taguchi method was employed to optimize the synthetic conditions for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(29 citation statements)
references
References 33 publications
(49 reference statements)
0
29
0
Order By: Relevance
“…Superabsorbent hydrogels (SHs) are water insoluble three-dimensional crosslinked polymer network that can absorb and retain great amount of aqueous solutions or biological fluids within own structure even under certain pressure (Bao, Ma & Li, 2011;Tally & Atassi, 2015). The good swelling and water retention capacity as well as desirable biodegradability of SHs make them able to be applied in various fields such as agriculture (Curcio & Picci, 2008), hygiene products (Kosemund, Schlatter, Ochsenhirt, Krause, Marsman & Erasala, 2009), wastewater treatment (Kaşgöz, Durmuş & Kaşgöz, 2008), tissue engineering (Wang, Strand, Du & Vårum, 2010), and drug delivery systems (Merino, Martín, Kostarelos, Prato & Vázquez, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Superabsorbent hydrogels (SHs) are water insoluble three-dimensional crosslinked polymer network that can absorb and retain great amount of aqueous solutions or biological fluids within own structure even under certain pressure (Bao, Ma & Li, 2011;Tally & Atassi, 2015). The good swelling and water retention capacity as well as desirable biodegradability of SHs make them able to be applied in various fields such as agriculture (Curcio & Picci, 2008), hygiene products (Kosemund, Schlatter, Ochsenhirt, Krause, Marsman & Erasala, 2009), wastewater treatment (Kaşgöz, Durmuş & Kaşgöz, 2008), tissue engineering (Wang, Strand, Du & Vårum, 2010), and drug delivery systems (Merino, Martín, Kostarelos, Prato & Vázquez, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…To solve these problems, the semi-interpenetrated polymer network (semi-IPN) was introduced. Semi-IPN is a way of blending two polymers, in which the linear polymer chains are diffused into a preformed polymer network to produce an additional noncovalent interaction between the two polymers without forming chemical bonds . The product generated by the semi-IPN technology usually exhibited surprising performances superior to either single polymer, namely, the semi-IPN structure can improve the swelling capacity, mechanical stability, and the specific surface area of the product .…”
Section: Introductionmentioning
confidence: 99%
“… 26 Parts of the N released could be confined in the hydrogel due to the improved internal surface area and well-developed pore channels of SBS- g -P(AA/AM). 27 Xiang et al also reported similar results for a UF-loaded kaolin- g -poly(acrylic acid- co -acrylic amide) hydrogel in soil. 8 …”
Section: Resultsmentioning
confidence: 61%